EFEKTIVITAS PENERAPAN METODE TAKRIR UNTUK MENINGKATKAN KEMAMPUAN TAHFIDZ ALQURAN PADA SANTRI PONDOK PESANTRENATTIBYAN BELOPA KABUPATEN LUWU - Muqayyid; Bunyamin, Andi; Wahab, Abdul; Mustamin; Syahrul, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of implementing effective learning methods to improve students' Qur'an memorization ability. The Takrir method emphasizes systematic repetition to strengthen memory retention and maintain long-term memorization. This study aimed to analyze the effectiveness of the Takrir method in improving the Qur'an memorization ability of ninth-grade students at Attibyan Islamic Boarding School, Belopa, Luwu Regency. A descriptive qualitative approach was employed. The research participants consisted of the head of the Islamic boarding school, tahfidz teachers, dormitory supervisors, and ninth-grade students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings revealed that the Takrir method was systematically implemented through individual repetition, group repetition, teacher-guided repetition, repetition during prayer, tasmi', and memorization submission sessions. The implementation of the Takrir method proved effective in improving students' Qur'an memorization ability, as reflected in increased memorization fluency, fewer recitation errors, stronger retention of previously memorized verses, and greater self-confidence during memorization assessments and prayer leadership. The effectiveness of the method was supported by students' discipline, continuous teacher supervision, a conducive boarding school environment, and regular memorization evaluation. Therefore, the Takrir method can serve as an effective instructional strategy for improving the quality of Qur'an memorization in Islamic boarding schools.